Evaluation of the possibilities to use the photogrammetric method to determine the course of boundaries of cadastral parcels during the modernization of the cadastre - Buśko, Małgorzata (International Conference “Environmental Engineering”, 2017)
In Poland, there are still many cadastral districts with the outdated database of the real estate cadastre. The situation which is particularly unfavorable occurs in southern Poland, on the territory of the former Austrian cadastre. This study presents a procedure for the comprehensive modernization of the real estate cadastre, carried out in numerous cadastral districts in the years 2014–2015, as part of the national project: Development of an Integrated Real Estate Information System. The modernization of the cadastre carried out in Gorlice district, province of Malopolska, served as an example to analyze the difficulties associated with the transformation of the analog materials and cadastral documents contained in the geodetic and cartographic documentation center database, often dating back to the times of the Austrian partition, into cadastral data in the electronic form, valuable in terms of accuracy and quality. The article presents the stages of determining the course of parcel boundaries, performed with the use of modern pho togrammetric method. This method significantly accelerates the works related to the modernization, however, it is not flawless. Nevertheless, this is the method of the future, which definitely shortens the task performance time. The conclusions which were formulated therefrom can accelerate and streamline the modernization process of the cadastre using photogrammetric measurements to determine the course of boundaries of the cadastral parcels in the sub sequent modernizations of the cadastre, as planned in Poland.
Keywords: boundaries of cadastral parcels; modernization of the cadastre; photogrammetry; real estate cadastre